PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK MOBIL TOYOTA AVANZA (Study kasus pada PT. Agung Automoll cabang Jambi) - Ahmad Tarmizi (Universitas Batanghari Jambi, 2015)
In this study using the method of survey the survey method, i.e. the method of research that takes samples from a population and use questionnaires as a means of collecting data and information relevant to the problem that dieliti. The population in this research the entire consumer by 2013 with a total of 1047 samples as much as much as 100 respondents. Analysis tools are used multiple linear regression Equations is to look at the influence of the brand image and product quality of consumers buying products car Toyota avanza.Based on the results of a multiple linear regression brand image (X 1) of 0.047 stated that any addition of 1% of the value of the X 1 will boost consumer buying decisions (Y) of 04,7%. Based on test results obtained partial degrees of freedom (df) = 97, α 0.05 thus criteria against the decision of consumers buy are: t calculate the t table 1.985 0.680 <, so the second hypothesis H0 Statement accepted and rejected the H1, which means partially brand image does not affect the consumer's decision to buy.the results of the analysis of the determination of the value of the results obtained koefisiendeterminasi R2 (R Square) 0.69, in other words the brand image (X 1) and product quality (X 2) together affect consumer purchasing decisions (Y) 69.1% is 30.9% while the rest were caused by factors other than the variables examined. And simultaneous test berdasarka (test F) obtained results value f calculate the significance level at 105.984 5% (0.05 < 0.000) acquired f table 3.09. Value fhitung > 105.984 3.09 table f, then H0 is rejected and the H1 is accepted so that it can be said that the whole brand image and the variable quality of products simultaneously affect the decisions of consumers buying products car Toyota avanza at PT Agung Automall branch of Jambi.The results of this analysis in accordance with the theory (kotler,2008:113) who said the link between the influence of the brand image and product quality towards keputuasan purchase can be inferred, the brand image will be one of the choice of the consumer to use the product, while the quality of the product will give you satisfaction and comfort for URkonsumen.dan that support this research results from a previous study that dilkakukan by sulistywati (2012) the influence of the brand image and product quality towards keputsan purchase acer laptops , which acquired hassil test hypothesis f sebeasar 65.836 count and significance of 0.000.Key word: brand image, product, consumer